2023
DOI: 10.1002/hyp.14831
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐to‐tile drain connectivity and phosphorus transport: Effect of antecedent soil moisture

Abstract: Macropores connecting surface soils to tile drains can alter water and nutrient transport through the subsurface. In this study, laboratory rainfall simulations with artificial macropores combined with edge‐of‐field monitoring were used to evaluate surface‐to‐tile drain connectivity and phosphorus (P) transport as a function of antecedent moisture conditions. Laboratory rainfall simulations using repacked soil boxes with different macropore layouts (i.e., no macropore, surface‐connected macropores, and disconn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Event water fractions increased from 3%–7% during rainfall simulations 1–3 when leachate from these lysimeters was slow to negligible to 92% following the installation of the macropores in rainfall simulation 5. Previous studies using artificial macropores have also noted their strong influence on soil hydrology (Akay & Fox, 2007) and event water transport (Williams, Penn, et al, 2023). Only lysimeter 10 was similar to the magnitude of event water fraction observed in the artificial macropore lysimeters (Figure 4).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Event water fractions increased from 3%–7% during rainfall simulations 1–3 when leachate from these lysimeters was slow to negligible to 92% following the installation of the macropores in rainfall simulation 5. Previous studies using artificial macropores have also noted their strong influence on soil hydrology (Akay & Fox, 2007) and event water transport (Williams, Penn, et al, 2023). Only lysimeter 10 was similar to the magnitude of event water fraction observed in the artificial macropore lysimeters (Figure 4).…”
Section: Discussionmentioning
confidence: 92%
“…Rapid mobilization of pre‐event water has been reported in tile‐drained fields because of matrix‐macropore interaction (i.e., preferential flow of old water; Klaus et al, 2013). Laboratory soil column studies with artificial macropores have also found that 9% of water transported through the macropore was pre‐event water (Williams, Penn, et al, 2023). Results from the current study therefore indicate that soil physical properties such as soil texture and infiltration rate may be more important than rainfall intensity for determining the mixing (and subsequent transport) of water in the shallow vadose zone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of the magnitude, intensity, and location of precipitation are all lost, especially in larger watersheds (Singh, 1997), since precipitation is a basin‐wide and multi‐year seasonal average in this study. Moreover, the amount of runoff generated by precipitation can also be influenced by antecedent soil moisture, which can increase the variability of an area's runoff response (Tarasova et al, 2018; Williams et al, 2023). The multivariate regression found that the strength of the relationship between ETₒ and RBI was weak and insignificant.…”
Section: Discussionmentioning
confidence: 99%